Evaluation of User Experience in Kiffah Interactive Learning Media Using the User Experience Questionnaire – Short (UEQ-S) - Khoirun Niswati Ulya; Ema Laila; Meiyi Darlies (Jurnal Ilmiah Multimedia dan Komunikasi, 2026)
Interactive learning media represents one of the most promising innovations for increasing student engagement in the learning process. Kiffah is an interactive learning medium in the form of a digital comic developed to help grade X students understand Fiqh, particularly the Muamalah chapter. Despite the growing adoption of interactive media in Islamic religious education, empirical UX evaluations of such applications using standardized instruments remain scarce in the literature. This study addresses that gap by evaluating the user experience (UX) of the Kiffah interactive learning media using the User Experience Questionnaire Short (UEQ-S), offering novel evidence on how a domain-specific educational comic application performs against international UX benchmarks. Thirty-five grade X Madrasah Aliyah students participated as respondents. Data were collected through media trials followed by UEQ-S administration, measuring Pragmatic Quality and Hedonic Quality dimensions. Results show that Kiffah obtained a score of 1.650 in Pragmatic Quality (Good), 1.571 in Hedonic Quality (Good), and 1.611 overall (Excellent), placing it among the top 10% of products in the UEQ benchmark dataset. These findings confirm that Kiffah delivers a positive and engaging user experience at the prototype stage. The study contributes practical design insights for developers of Islamic educational digital media and recommends further evaluation with larger and more diverse samples.